The role of mitophagy in metabolic diseases and its exercise intervention - Tang, Shaokai; Geng, Yuanwen; Lin, Qinqin (Frontiers in Physiology, 2024)
Mitochondria are energy factories that sustain life activities in the body, and their dysfunction can cause various metabolic diseases that threaten human health. Mitophagy, an essential intracellular mitochondrial quality control mechanism, can maintain cellular and metabolic homeostasis by removing damaged mitochondria and participating in developing metabolic diseases. Research has confirmed that exercise can regulate mitophagy levels, thereby exerting protective metabolic effects in metabolic diseases. This article reviews the role of mitophagy in metabolic diseases, the effects of exercise on mitophagy, and the potential mechanisms of exercise-regulated mitophagy intervention in metabolic diseases, providing new insights for future basic and clinical research on exercise interventions to prevent and treat metabolic diseases.